A Systematic Review and Analysis of the Quality of Randomized Controlled Trials Comparing Infrapatellar and Suprapatellar Approach for Nailing of Tibial Fractures. Issue 10 (October 2021) - Chan, Andrew; Pisquiy, John; Piscoya, Andres S.; Clark, DesRaj; Dunn, John C
Abstract : Objectives: To evaluate the quality of evidence presented in prospective randomized controlled trials (RCTs) regarding suprapatellar versus infrapatellar approaches to tibia intramedullary nails using grading systems other than Oxford Levels of Evidence (LOE). Data Sources: A systematic review was performed using the phrases "tibial nail OR tibia OR intramedullary" AND "suprapatellar OR infrapatellar" AND "approach OR insertion" to search the PubMed database between 1999 and 2018 filtering for English language and full articles. Study Selection: Included articles were prospective trials that compared infrapatellar and suprapatellar approaches to tibial intramedullary nails in adult patients. Data Extraction: Studies were evaluated and scored by 2 independent observers using 3 different systems: Oxford LOE, Modified Coleman Methodology Score, and Revised Consolidated Standards of Reporting Trials (CONSORT). Data Synthesis: Comparison for grading between observers was compared with a correlation coefficient and kappa statistic. Conclusions: RCTs are historically regarded as the gold standard for establishing principles of evidence-based medicine. However, our evaluation of the evidence shows that though they followed the Oxford LOE, RCTs were considered poor by the other 2 methods. The majority of studies that were included in our review were considered poor using the Modified Coleman and CONSORT systems. Half the articles supported suprapatellar tibial nailing over the infrapatellar approach, whereas other half demonstrated equivocal results between the 2 techniques. This study highlights the importance of evaluating studies judiciously regardless of their study design or level of evidence. Abstract : Supplemental Digital Content is Available in the Text.